Optimizing the Duct Shape and Location for Improving Performance of Darrieus Wind Turbine (International Journal of Current Engineering and Technology, 2015)
This article studies the possibility of increasing the power output of Darrieus wind turbine using an optimized duct using Genetic Algorithm (GA) or a straight duct. Computational fluid dynamics (CFD) studies were conducted to optimize the geometrical parameters of the duct in order to achieve maximum possible wind velocity increase, keeping into account the size and cost constraints of the device. In this study, the resulted duct shape decreases the variation in torque over a cycle by appropriately directing the flow upstream and downstream the turbine while increasing power coefficient. At the operating point obtained maximum power, which is at a tip-speed ratio of 3.29, use of optimized duct makes the torque ripple (TRF) decreased by 84% from un-ducted wind turbine and the maximum power coefficient (Cp) is increased by 123%. By choosing the position of the turbine in the duct appropriately, it is shown that the minimum torque ripple and maximum power coefficient were observed when the turbine center coincided with the throat of the duct. Both straight ducted wind turbine and optimized ducted wind turbine have close maximum power coefficient, but optimized duct makes the torque ripple (TRF) decreased by 80% from straight ducted wind turbine wind turbine.
Keywords: Darrieus wind turbine; Genetic Algorithm; Optimum Wind duct geometry; Computational fluid Dynamics